'An Awfully Nice Job'. Kathleen Kenyon as Secretary and Acting Director of the University of London Institute of Archaeology, 1935–1948. Issue 1 (5th December 2018) - Meheux, Katie
Abstract : This article presents an assessment of the administrative career of Kathleen Kenyon. It examines her involvement in the new Institute and wider British archaeological community as well as assessing her working life within the context of the increasing professionalisation of archaeological organisations between the wars, and the role played in this by female administrators. The behaviours and actions of Kenyon and those around her are also evaluated within the context of wider contemporary attitudes to and about women. Finally, Kenyon's role in women's archaeological practice and women's contributions to archaeological culture between the wars is considered.